Importance of ventricle-to-brain ratio (VBR) and volume of CSF drainage in the treatment of very low pressure hydrocephalus - Houlden, D; Li, M; Portman, S (Canadian journal of neurological sciences, 2015)
Introduction: Low pressure hydrocephalus is a known complication of prolonged hydrocephalus sometimes treatable with continued low-pressure drainage at subatmospheric pressures. Clarke et. al. and Filipidis et. al. have reported poor outcomes when treating very low pressure hydrocephalus (VLPH). We present 4 cases of very low pressure hydrocephalus (VLPH) following transnasal endoscopic resection of suprasellar lesions and hypothesize that poor prognostic cases can be identified thereby avoiding prolonged futile treatments. Methods: We performed a retrospective chart review of 4 cases of VLPH and tried to identify metrics contributing to successful treatment. We examined the Pearson correlations between Glasgow Coma Scale and ventricle-to-brain ratio (VBR); volume of CSF drained; net fluids; and serum sodium, urea, and creatinine. Results: Our investigation reveals that Glasgow Coma Score is positively correlated with increased CSF drainage and negatively correlated with increased ventricle-to-brain ratio. The most important determinant of good outcome is brain compliance as measured by the brain’s ability to maintain a good GCS score in the face of wide ranges in ventricle-to-brain ratio (VBR). Conclusion: We propose that futile prolonged subatmospheric drainage be avoided by declining treatment in patients who have ventriculitis and patients who have a narrow range of ventricle-to-brain ratio (VBR) concurrent with a good neurological examination.